Long-term antihypertensive treatment improves ventricular-arterial interaction in hypertensive patients: a 3-year follow-up study. (25th November 2020) - Ikonomidis, I; Tzortzis, S; Triantafyllidi, H; Thymis, J; Frogoudaki, A; Vrettou, A.R; Iliodromitis, E
Abstract: Background: We investigated the effects of antihypertensive treatment on vascular function, longitudinal deformation and ventricular-arterial interaction in hypertensives. Methods: In 200 untreated patients with arterial hypertension (age 52.5±11.6 years, 56% females), we measured at baseline and after a 3-year of antihypertensive treatment (160 received ACEi± diuretics and 40 CCBs± diuretics): a) 24h ambulatory blood pressure b) Carotid-femoral pulse wave velocity (PWV) b) Coronary flow reserve (CFR), LV mass index (LVMI), the global longitudinal strain (GLS). We calculated the ratio of PWV/GLS (-m/sec%) reflecting the ventricular-arterial interaction. Results: Compared to baseline, there was an improvement of GLS (−19.9±3.4 vs. −18.7±3.1%), post-treatment. In parallel, there were improvement in CFR (2.72±0.61 vs. 2.55±0.64), PWV (10.3±1.9 vs. 11.2±2.1 m/s), LVMI and PWV/GLS (−0.539±0.146 vs. −0.618±0.178 -m/sec%) (p<0.01 for all comparisons). By multivariate analysis, the reduction of 24h meanBP as well as PWV independently determined the respective improvement of GLS (b=0.478, b=0.248, respectively, p<0.001). By ANOVA, the interaction term between changes of all the above parameters and antihypertensive treatment (ACE inhibitors vs calcium channel blockers) was not significant (p>0.05). Conclusions: Long-term optimal blood pressure control with ACE inhibitors and CCBs improves LV longitudinal deformation along with reduction of arterial stiffness, leading to improved ventricular-arterial interaction in hypertensives. Funding Acknowledgement: Type of funding source: None